O ERP como ferramenta da controladoria: um estudo de caso na indústria de mineração do estado do Ceará - Sampaio Neto, Francisco Bastos (2007)
The growth of information techniques has began in the 90’s thanks to the diffusion of ERP systems (Enterprise Resource Planning), more frequently known as Management Integrated Systems, which have some advantages in comparison with the systems developed by private companies. In an empirical research, this work intended to verify the use of ERP systems as a tool for controlling processes in a typical medium-size company of the mining field. The first part of the bibliographic data raising in this work is about the theoretical construct in what is related mediumsize companies’ management. A study of the concepts and main models of economical management and costs was done through bibliographic researches. There was also a study on the concepts of financial management and its functions and the controller’s part in it. The second part of the theoretical referral is about the concepts, characteristics, benefits and problems related to the utilization of the ERP system as a support tool to business management. Among the obtained results, the timeline and the reliability on information to the manager, the supplier’s rationalization of administrative activities, the safety and access to information, as well as the permanent technological actualization, by the manager, are highlighted as a benefit. Among the verified difficulties, the highlighted ones are dependence of a unique supplier for the management system, the functional cover (if the system fails, all the company stops), information chain (a routine may affect the other) and the system’s slowness when it is necessary to process the transactions at the same time other users are using it. It was also verified the importance of management model definitions for the system’s previous configuration, before its usage.